2020
DOI: 10.1101/2020.04.09.20059113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmission routes of Covid-19 virus in the Diamond Princess Cruise ship

Abstract: 285 Words) Main text (2426 words) AbstractBackground: An outbreak of COVID-19 occurred on the Diamond Princess cruise ship in January and February 2020. We analysed information about cases to infer transmission dynamics and potential modes of transmission. Methods:We collected the daily number of 197 symptomatic cases, and that of the 146 passenger cases in two categories, i.e. those who stayed and did not stay in the same stateroom. We retrieved the quarantine details and the ship's 14-day itinerary. We searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 9 publications
0
31
1
4
Order By: Relevance
“…According to Zhang et al, the main route for transmission was from person to person, but other routes, including aerosol transmission via central air supply or drainage systems, could not be excluded [42]. The studies of Xu et al [43] and Mizumoto and Chowell [44] on the same outbreak, led to the opposite conclusion. Most of the cases originated by passenger-to-passenger transmission through close contact and fomites.…”
Section: Resultsmentioning
confidence: 99%
“…According to Zhang et al, the main route for transmission was from person to person, but other routes, including aerosol transmission via central air supply or drainage systems, could not be excluded [42]. The studies of Xu et al [43] and Mizumoto and Chowell [44] on the same outbreak, led to the opposite conclusion. Most of the cases originated by passenger-to-passenger transmission through close contact and fomites.…”
Section: Resultsmentioning
confidence: 99%
“…A paper published in Infectious Disease Modelling on 29 February found that the spread of covid-19 on the Diamond Princess fell substantially after passengers were confined to their cabins on 5 February at the request of the Japanese government 4. A preprint posted by researchers in China on 14 April has corroborated those findings 5. The researchers examined data on 197 people with symptoms on the ship, using records published by Japanese authorities.…”
Section: Early Datamentioning
confidence: 95%
“…[43] The same year,X ua nd co-authors developed as ynthetic route for the preparation of talazoparib in 30 gs cale by chiral resolution (Scheme22). [44] Methyl3 -amino-5-fluorobenzoate (124)a nd 3-(4-fluorophenyl)-3-oxopropanoic acid (125)w ere selected as the startingm aterials. Cyclization reaction of 124 with 125 and reduction with NaBH 4 gave intermediate 126.…”
Section: Talazoparib (Talzenna)mentioning
confidence: 99%